2022
DOI: 10.3390/genes13101732
|View full text |Cite
|
Sign up to set email alerts
|

Integrative System Biology Analysis of Transcriptomic Responses to Drought Stress in Soybean (Glycine max L.)

Abstract: Drought is a major abiotic stressor that causes yield losses and limits the growing area for most crops. Soybeans are an important legume crop that is sensitive to water-deficit conditions and suffers heavy yield losses from drought stress. To improve drought-tolerant soybean cultivars through breeding, it is necessary to understand the mechanisms of drought tolerance in soybeans. In this study, we applied several transcriptome datasets obtained from soybean plants under drought stress in comparison to those g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Yet, functional characterization of relevant genes is often missing in gene discovery, which is absolutely required for crop improvement. Many systematic studies have identified a number of candidate genes for growth and water stress response, providing useful genetic resources for functional analyses and future development of improved soybean ( Le et al., 2011 ; Le et al., 2012 ; Neves-Borges et al., 2012 ; Chai et al., 2015 ; Ha et al., 2015 ; Song et al., 2016 ; Hussain et al., 2017 ; Melo et al., 2018 ; Zhou et al., 2020 ; Shahriari et al., 2022 ; Xuan et al., 2022 ). However, the functionality of majority of these candidate genes is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, functional characterization of relevant genes is often missing in gene discovery, which is absolutely required for crop improvement. Many systematic studies have identified a number of candidate genes for growth and water stress response, providing useful genetic resources for functional analyses and future development of improved soybean ( Le et al., 2011 ; Le et al., 2012 ; Neves-Borges et al., 2012 ; Chai et al., 2015 ; Ha et al., 2015 ; Song et al., 2016 ; Hussain et al., 2017 ; Melo et al., 2018 ; Zhou et al., 2020 ; Shahriari et al., 2022 ; Xuan et al., 2022 ). However, the functionality of majority of these candidate genes is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used bioinformatic tools such as differential gene expression analysis and homologous sequence similarity to the genes with known function in rice and Arabidopsis to identify candidate genes for root growth and water-deficit tolerance in soybean. These systematic-based analyses detected transcriptional factors of the MYB, bHLH, AP2-EREBP, NAC, WRKY, bZIP, and C2H2-zinc finger gene families as prime factors ( Le et al., 2011 ; Le et al., 2012 ; Neves-Borges et al., 2012 ; Chai et al., 2015 ; Ha et al., 2015 ; Song et al., 2016 ; Hussain et al., 2017 ; Melo et al., 2018 ; Zhou et al., 2020 ; Shahriari et al., 2022 ; Xuan et al., 2022 ). However, the majority of these studies lack the functional characterization of these candidate genes.…”
Section: Introductionmentioning
confidence: 99%
“…To find the upstream flanking region of DEGs (1000 bp) [ 74 ], a BLAST against the Ensemble plant database was performed [ 75 ]. Then, the MEME [ 76 ] database was used to identify the conserved cis-acting elements.…”
Section: Methodsmentioning
confidence: 99%
“…Meta-analyses are efficient approaches to the identification of important genes in abiotic stress responses. Recently, these bioinformatic analyses uncovered important abiotic stress targets in soya, wheat, and rice [ 200 , 201 , 202 ]. The results of the transcriptomic studies, which are available in the Expression Atlas database, provide a rich resource that allows analyses and comparisons of the effects of different stressors [ 203 ].…”
Section: Similarities Among Abiotic Stresses and Their Potential Cros...mentioning
confidence: 99%